Pengaruh Kedisiplinan Guru Aqidah Akhlak Terhadap Motivasi Belajar Siswa Kelas XI Di Man 2 Kabupaten Bogor - Hidayah, Wafa; Supriadi, Dedi; Rosidah, Noneng Siti (Peneliti.net, 2024)
The problem behind this research is the low motivation to learn which is characterizedby the occurrence of violations committed by students during learning activities at MAN 2 Bogor Regency. In addition, there are also several phenomena in various regions regarding violations committed by students to teachers at school. The objectives of this study are (1) to determine the discipline of aqidah akhlak teachers at MAN 2 Bogor Regency, (2) to determine the learning motivation of grade XI students at MAN 2 Bogor Regency, (3) to determine whether there is an influence between the discipline of aqidah akhlak teachers on the learning motivation of grade XI students at MAN 2 Bogor Regency. This research uses quantitative methods where the data collection process is carried out by distributing research questionnaires to 63 grade XI students at MAN 2 Bogor Regency. The results showed that: (1) the discipline of moral aqidah teachers obtained a total average value of 61.93 these results indicate that the discipline of moral aqidah teachers in these schools is included in the good category. (2) the learning motivation of class XI students obtained a total averagevalueof 56.57, this shows that the learning motivation of class XI students is included in thegood enough category. (3) the results of the simple linear regression test 0.000 <0.05show that there is a positive and significant effect of the discipline of the aqidah akhlak teacher on the learning motivation of class XI students at MAN 2 Bogor Regency, so Ha is accepted and Ho is rejected. Therefore, if schools want to increase student learning motivation, one of the things that must be considered is the discipline of a teacher.